Effects of oxidizer structure on thermal and combustion behavior of Fe2O3/Zr thermite. (29th October 2021) - Li, Chunhong; Kang, Xiaoli
Abstract: Performance of MOF-derived micrometer porous Fe2 O3 as the oxidizer in Zr-fuelled thermite is compared with commercial nano-sized Fe2 O3 by characterizing thermal and combustion behavior of Fe2 O3 /Zr mixture via differential scanning calorimetry, optical emission measurement as well as composition and morphology analysis on condensed combustion products. Results show that thermal behaviors of Fe2 O3 /Zr with a slow heating rate have little difference regardless of the kind of Fe2 O3 . However, MOF-derived micrometer porous Fe2 O3 show an obvious superiority in enhancing combustion of Fe2 O3 /Zr heated by a high rate. Combustion reactions of Fe2 O3 /Zr under high heating rates are probably rate-controlled by condensed reaction. The better performance of MOF-derived Fe2 O3 is attributed to its larger contact area with Zr particle in that micrometer porous Fe2 O3 particles are easily broken into primitive nano-sized particles, which effectively avoid the agglomeration of oxidizer. The MOF-derived Fe2 O3 particles obtained at calcination temperature of 550 °C enable the best combustion performance of Fe2 O3 /Zr thermite. This should be because the crystallinity and porous structure of 550 °C-Fe2 O3 are more favorable for the mass transfer process during high-rate combustion.